Comprehensive bioinformatics analysis of key miRNAs and signaling pathways in the body fluids of human knee osteoarthritis: miRNAs and signaling pathways in the body fluids of knee OA - Malakootian, Mahshid; Gholipour, Akram; Oveisee, Maziar (Cellular and Molecular Biology, 2023)
Osteoarthritis (OA) is one of the principal causes of chronic joint disease with a series of pathological features. The present study aimed to identify key microRNAs (miRNAs) and signaling pathways in OA biological fluids to explain the potential mechanisms underlying the disease and introduce OA biomarkers using computational analysis. Differentially expressed microRNAs (DEmiRNAs) in the serum, plasma, and synovial fluids of OA patients were identified using the GEO2R, limma, and DESeq2 packages in the R software based on the dataset from GSE151341, GSE105027, and GSE126677. The gene ontology (GO) enrichment, Kyoto Encyclopedia of Genes and Genomes (KEGG), and network construction analyses were performed for overlapping DEmiRNAs. Forty DEmiRNAs overlapped in the plasma, serum, and synovial fluids of OA patients. The expression patterns of the DEmiRNAs in the serum and plasma were almost the same, while they were reversed in the synovial fluid. Differentially expressed hsa-miR-146a-5p and hsa-miR-335-5p miRNAs showed downregulation in all 3 OA sample types. According to enrichment analysis regarding OA pathogenesis, the signaling pathways of TGF-β, Hippo, FoxO, PI3K-Akt, and mTOR were significant, with hsa-miR-146a-5p and hsa-miR-335-5p involved in their regulation. The present informatics study for the first time provides insights into the potential diagnostic targets of OA by analyzing overlapping miRNAs and their relevant signaling pathways in human knee fluids (serum, plasma, and synovial fluids).